(3MGTjI TjN RGOg Ydi JaSjQ GdHjVGhjs - (3ehdGfG RGOg, eMeO Hf CMeO (B((3, J (B859(3g`(B)s
(3ChdgG (B:s
(3MeGdI GdMWH hCLGH Yfg HKdGKI ChLg GdChd(B: (3Cf djS GdeQGO HGdMWH GdMWH Hd GdeQGO Hg eG MedJg ef GdBKGe hGdChRGQs
(3BNQgG (B:s
(3hEf SdGeI GdHOf ef Jdc GdBaGJ hEf cGfJ CehQG eJYOOI djSJ HJdc GdeKGHI aj GdGgJeGe hGdeWdhHjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf (B2/1475s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
Keywords: (3GdJaSjQ hYdhe GdbQBfs